Thai Students' Experiences of Online Learning at Indonesian Universities in the Time of the COVID-19 Pandemic - Ferdiansyah, Sandi; Supiastutik,; Angin, Ria (Journal of International Students, 2020)
The present interview study reports on eight Thai undergraduate students’ experiences of online learning at three different Indonesian universities based in East Java, Indonesia. Semi-structured interviewing was designed based on the sociocultural framework proposed by Ma (2017) to elucidate the students’ voices of online learning experience. The data garnered from online interviewing were transcribed and interpreted using thematic content analysis. The study elicits three important data themes: the agility of the student participants to adapt online learning to suit their learning needs, the participants’ strategies to build learning autonomy, and the participants’ ability to sustain their learning motivation. This study stresses the important roles of such other agents as teachers, parents, and friends in providing international students with mental and emotional support to help them get through COVID-19 affected online learning.